Cholesterol in mouse retina originates primarily from in situ de novo biosynthesis - Joseph B. Lin; Natalia Mast; Ilya R. Bederman; Yong Li; Henri Brunengraber; Ingemar Björkhem; Irina A. Pikuleva (Journal of Lipid Research, 2016)
The retina, a thin tissue in the back of the eye, has two apparent sources of cholesterol: in situ biosynthesis and cholesterol available from the systemic circulation. The quantitative contributions of these two cholesterol sources to the retinal cholesterol pool are unknown and have been determined in the present work. A new methodology was used. Mice were given separately deuterium-labeled drinking water and chow containing 0.3% deuterium-labeled cholesterol. In the retina, the rate of total cholesterol input was 21 ¼g of cholesterol/g retina • day, of which 15 ¼g of cholesterol/g retina • day was provided by local biosynthesis and 6 ¼g of cholesterol/g retina • day was uptaken from the systemic circulation. Thus, local cholesterol biosynthesis accounts for the majority (72%) of retinal cholesterol input. We also quantified cholesterol input to mouse brain, the organ sharing important similarities with the retina. The rate of total cerebral cholesterol input was 121 ¼g of cholesterol/g brain • day with local biosynthesis providing 97% of total cholesterol input. Our work addresses a long-standing question in eye research and adds new knowledge to the potential use of statins (drugs that inhibit cholesterol biosynthesis) as therapeutics for age-related macular degeneration, a common blinding disease.